Use of combined picosecond 1064nm and thulium laser 1927nm in melasma treatment – case report - Kozinska, Urszula; Gras-Ozimek, Jordi (Journal of Education, Health and Sport, 2022)
Melasma is an acquired, chronic skin pigmentation disorder that affects mainly women and can significantly affect the quality of life and self-esteem of patients. Many therapeutic procedures have been described in the literature, nevertheless the disease is difficult to treat. A case report. The paper presents a case of successful laser treatment in a 44-year-old woman with a long history of facial skin discoloration of the type of melasma. The patient was treated with combined laser therapy in the area of ​​facial discoloration with a picosecond laser and a thulium laser. Aim The aim of this study is to draw attention to the possibility of using laser therapy in the treatment of melasma-type skin hyperpigmentation. In this article, we describe a case of brightening of a melasma-type discoloration during a single laser treatment combining the use of a 1064nm picosecond laser and a 1927nm thulium laser, in order to meet interests of patients and physicians in the use of laserotherapy in the treatment of discoloration, especially in patients who do not tolerate well the side effects of pharmacological therapies. Conclusions. The use of laser therapy, with particular emphasis on the picosecond and thulium laser, can be an important and effective element in the treatment of melasma-type hyperpigmentation of the skin.